Structural transformation and intertemporal evolution of real wages, machine use, and farm size–productivity relationships in Vietnam - Liu, Yanyan; Violette, William; Barrett, Christopher B. (International Food Policy Research Institute, 2016)
This paper explores the evolution of real agricultural wages, machinery use, and the relationship between farm size and productivity in Vietnam during its dramatic structural transformation over the course of the 1990s and 2000s. Using six rounds of nationally representative household survey data, we find strong evidence that the inverse relationship between rice productivity and planting area attenuated significantly over this period and that the attenuation was most pronounced in areas with higher real wages. This pattern is also associated with sharp increases in machinery use, indicating a scale-biased substitution effect between machinery and labor. The results suggest that rural-factor market failures are receding in importance, making land concentration less of a cause of concern for aggregate food production.